Peran Ayah sebagai Pelindung dan Panutan dalam Mencegah Perilaku Kenakalan Remaja Laki-Laki? - Syachdan Rengga; Nina Yuliana (Jurnal Ilmu Komunikasi Balayudha, 2026)
Fathers play a crucial role as protectors and role models in preventing delinquency among boys aged 15 to 18, including behaviours such as fighting and conflict, truancy and smoking.This study shows that physical protection, social supervision, and good communication from the father can reduce the risk of such deviant behaviors. Therefore, a father who serves as a role model in moral, religious, and academic aspects helps shape a more positive character in adolescents. This discussion emphasizes the need for fathers to actively support the development of male adolescents.